2021
DOI: 10.1038/s41379-020-00690-w
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse expression of MUC6 defines a distinct clinicopathological subset of pulmonary invasive mucinous adenocarcinoma

Abstract: Invasive mucinous adenocarcinoma (IMA) of the lung is a unique variant of lung adenocarcinoma.Aberrant mucin expression is associated with cancer development and metastasis. However, the clinicopathological significance of mucin expression in IMA is not fully understood. Herein, we evaluated the clinicopathological, immunohistochemical, and molecular characteristics of 70 IMA tumors. EGFR, KRAS, GNAS, and TP53 mutations were assessed by PCR-based sequencing.Next-generation sequencing was used to assess cases w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 44 publications
1
25
0
Order By: Relevance
“…5) or anchored multiplex PCR (6), previous studies failed to reveal a mitogenic driver alteration in the majority of such cases. Notably, the early studies frequently used molecular techniques with limited analytical sensitivity for KRAS mutation detection (3,7,8), and more recent studies using next-generation sequencing (NGS) techniques only examined mutations and fusions, but not copy-number alterations (5,6,10).…”
Section: Introductionmentioning
confidence: 99%
“…5) or anchored multiplex PCR (6), previous studies failed to reveal a mitogenic driver alteration in the majority of such cases. Notably, the early studies frequently used molecular techniques with limited analytical sensitivity for KRAS mutation detection (3,7,8), and more recent studies using next-generation sequencing (NGS) techniques only examined mutations and fusions, but not copy-number alterations (5,6,10).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, accumulating results indicate that MUC6‐positive or higher‐expressing cases showed preferable prognosis in gastric cancer, 36 colorectal cancer, 37 and pulmonary invasive mucinous adenocarcinoma. 38 We also examined MUC6 mRNA expression and prognosis of pancreatic ductal adenocarcinoma patients and found that higher mRNA levels were significantly correlated with favorable prognosis as compared with lower levels (Figure 5B ). The present study also strongly supports the idea that α4GnT and MUC6 exert tumor‐suppressive effects on two pancreatic cancer cell lines and suggests that α4GnT, or αGlcNAc, and MUC6 may also be good prognostic markers in pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…KRAS mutations have been linked to the clinicopathological, immunohistochemical and molecular characteristics of pulmonary invasive mucinous adenocarcinoma. 7 Because metastatic NSCLC harboring KRAS G12C can be treated with KRAS-targeting agents (e.g., sotorasib), the detection of KRAS subtypes using methods such as the Lung Cancer Compact Panel is essential for therapeutic decision-making. We strongly suspected lung cancer because of this finding, and recommended surgical resection.…”
Section: Discussionmentioning
confidence: 99%